2022
DOI: 10.1002/lary.30413
|View full text |Cite
|
Sign up to set email alerts
|

Mastoid Obliteration Decreases the Recurrent and Residual Disease: Systematic Review and Meta‐analysis

Abstract: Objective: Our study aims to evaluate the effectiveness of mastoid obliteration compared to the canal wall up (CWU) technique in cholesteatoma surgery based on the systematic review of the literature and the meta-analysis of the data.Methods: The systematic search was performed in four major databases (MEDLINE, Web of Science, Embase, and CENTRAL) on October 14, 2021. Studies comparing the CWU technique and mastoid obliteration were included. The exclusion criteria were less than 12 months follow-up, congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…
We would like to thank you for the opportunity to reply to Mr Faramarzi's valuable comment about our manuscript titled: Mastoid Obliteration Decreases the Recurrent and Residual Disease: Systematic Review and Meta-analysis. 1 We agree with many of their points, especially on the surgical heterogeneity of our analyses, which was mentioned in our study as a limitation. Mastoid obliteration is not yet universally accepted as a surgical technique, and there is no clear consensus regarding its indication.
…”
supporting
confidence: 87%
“…
We would like to thank you for the opportunity to reply to Mr Faramarzi's valuable comment about our manuscript titled: Mastoid Obliteration Decreases the Recurrent and Residual Disease: Systematic Review and Meta-analysis. 1 We agree with many of their points, especially on the surgical heterogeneity of our analyses, which was mentioned in our study as a limitation. Mastoid obliteration is not yet universally accepted as a surgical technique, and there is no clear consensus regarding its indication.
…”
supporting
confidence: 87%
“…The main limitation of the technique is the inability to explore the mastoid cavity during follow-up with the risk of developing a “silent cholesteatoma”, making radiological follow-up essential. This technique has become popular in the last two decades with the development of non-EPI DW-MRI, which facilitates detection of cholesteatoma in obliterated or reconstructed cavities 30 . Surgical techniques and materials used for obliteration and reconstruction vary widely.…”
Section: Mastoid Obliterationmentioning
confidence: 99%
“…However, there is still no consensus around the technique, type of material to be used, or the ideal timing for surgery (simultaneous or during revision surgery) 32 . A systematic review and meta-analysis by Illes et al 30 collected data from 2077 operations from 11 articles to evaluate the effectiveness of mastoid obliteration compared to the CWU technique. The results demonstrated that mastoid obliteration significantly reduced cholesteatoma recidivism (Odds Ratio = 0.45, Confidence Interval = 0.26-0.8, p = 0.014).…”
Section: Mastoid Obliterationmentioning
confidence: 99%
“…
We read with great interest the meta-analysis by Illés et al 1 on the beneficial effect of mastoid obliteration over the canal wall-up technique for cholesteatoma surgery. The authors included 11 studies in the systematic review and 8 in the quantitative analysis, with a total of 1847 patients.
…”
mentioning
confidence: 99%